Trunk-to-peripheral fat ratio predicts a subsequent blood pressure in normal-weight pubertal boys: a 3-year follow-up of the Kitakata Kids Health Study - Katsuyasu Kouda; Masayuki Iki; Yuki Fujita; Harunobu Nakamura; Masami Hamada; Kazuhiro Uenishi; Mari Miyake; Toshimasa Nishiyama (Komiyama Printing Co. Ltd, 2020)
Abstract Background Limited evidence exists regarding the relationship between central-to-peripheral fat ratio measured by dual-energy X-ray absorptiometry (DXA) and subsequent cardiometabolic risk in both pediatric and adult populations. Methods The present cohort study investigated the relationship between DXA-measured body fat distribution and cardiometabolic parameters. The source population was 275 4th-6th graders (aged 9.6-12.6 years) in the northeast region of Japan (Shiokawa area in Kitakata). A 3-year follow-up was conducted to obtain complete information from 155 normal-weight children (87 boys and 68 girls). Normal-weight children were identified using sex- and age-specific international cut-offs for body mass index (BMI) based on adult BMI values of 25 kg/m2 and 18.5 kg/m2, respectively. Body fat distribution was assessed using the trunk-to-appendicular fat ratio (TAR) and trunk-to-leg fat ratio (TLR) measured by DXA. Results In boys, systolic blood pressure (SBP) at follow-up showed a significant relationship with TAR at baseline after adjusting for age, height, pubic hair appearance, SBP, and whole body fat at baseline (β = 0.24, P < 0.05), and SBP also showed a significant relationship with TLR after adjusting for confounding factors including whole body fat (β = 0.25, P < 0.05). In girls, there were no significant relationships between blood pressure and TAR/TLR. Conclusion Body fat distribution in normal-weight boys predicted subsequent blood pressure levels in adolescence. The relationship between fat distribution and blood pressure was independent of fat volume.